Accelerometer-measured physical activity in Norwegian adolescents. Results from The Fit Futures Study - Beldo, Sigurd (UiT The Arctic University of Norway, 2021)
This thesis examined the prevalence and patterns of accelerometer-measured physical activity in a cohort of urban-rural older adolescents in Northern Norway, participating in the Fit Futures Study. The thesis also assessed the validity of self-reported physical activity against accelerometer measurements, and explored the association between accelerometer-measured physical activity and subsequent change in five different measures of body composition over 2 years of follow-up. We found that less than 25 % of older adolescent boys and girls fulfilled the global physical activity recommendations. The self-reported physical activity questionnaire seems to be able to rank physical activity levels, and the validity is fairly stable across strata of sex, BMI, and education. However, the validity in providing information on absolute physical activity levels is limited. Minutes spent in baseline moderate-to-vigorous physical activity were not associated with subsequent changes in measures of body composition in neither sex. Sedentary time and light physical activity were associated with changes in lean body mass in girls, but not boys. The findings are interpreted in light of the substantial changes in habits and body composition that occur during adolescence. As few adolescents seem to adhere to the PA guidelines, there is a need for more research on how to promote and implement physical activity in a way that is tailored to adolescents.